Anti-HER3 Monoclonal Antibody Inhibits Acquired Trastuzumab-Resistant Gynecologic Cancers. (August 2016) - Li, Xinying; Duan, Yanting; Qiao, Chunxia; Zhou, Tingting; Yu, Ming; Geng, Jing; Feng, Jiannan; Shen, Beifen; Lv, Ming; Li, Yan
Background: Antibody resistance, both de novo and acquired, is usually related to high risk of recurrence and lower survival rate in gynecologic cancers. Prevention or reversal of the resistance often yields beneficial clinical results. It was reported that anti-human epidermal growth factor receptor 3 monoclonal antibody was effective against trastuzumab-resistant breast cancer cells. Here in our laboratory, an acquired trastuzumab-resistant ovarian cancer cell line, SKOV3-T, was established previously. Further, human epidermal growth factor receptor 3 was observed to be upregulated in this cell line by microarray detection, suggesting that the antagonist against human epidermal growth factor receptor 3 might be effective to inhibit the resistant cells. Methods: We developed an anti-human epidermal growth factor receptor 3 monoclonal antibody, LMAb3, and its affinity to bind human epidermal growth factor receptor 3 was calculated by the Biacore method. Preliminarily, LMAb3's antitumor activity was evaluated in vitro using cell growth/proliferation and clone formation assays in the breast cancer cell line MCF-7. Furthermore, LMAb3 was also evaluated for its inhibitory effect on the carcinogenicity of the SKOV3-T cells, which were induced to overexpress human epidermal growth factor receptor 3, both in vitro and in vivo . The possible underlying signal transduction mechanisms were also identified by Western blot in the MCF-7 and SKOV3-T cells. Results: LMAb3 was able to inhibit the cell growth/proliferation, clone, and tumor formation both in vitro (in the MCF-7 and SKOV3-T cells) and in vivo . The underlying mechanism of LMAb3 possibly involves inactivation of the HER family proteins (human epidermal growth factor receptor 1, human epidermal growth factor receptor 2, and especially human epidermal growth factor receptor 3) as well as the downstream mitogen-activated protein kinase and protein kinase B pathways. Conclusion: Our work suggests that satisfactory curative effects might be achieved with LMAb3 to treat the trastuzumab-resistant, human epidermal growth factor receptor 3-positive cases of gynecologic cancers.